2009
DOI: 10.1007/s00330-009-1525-0
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial chemoembolization (TACE) with mitomycin C and gemcitabine for liver metastases in breast cancer

Abstract: The purpose of this study was to evaluate the efficacy of transarterial chemoembolization (TACE) using different drug combinations in the treatment of breast cancer liver metastases in terms of local tumor control and survival rate. A total of 208 patients (mean age 56.4 years, range 29-81) with unresectable hepatic metastases of breast cancer were repeatedly treated with TACE at 4-week intervals. In total, 1,068 chemoembolizations were performed (mean 5.1 sessions/patient, range 3-25). The chemotherapy protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 42 publications
1
29
0
1
Order By: Relevance
“…In previous studies, the treatment outcome of TACE was evaluated for BCLM; patients treated with TACE had higher response rates and better survival (Li et al 2005;Schneebaum et al 1994;Vogl et al 2010). Li et al (2005) compared results of TACE (n = 28) and systemic chemotherapy (n = 20) and concluded that there was statistically significant differences between the two groups in terms of response rates and survival rates.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In previous studies, the treatment outcome of TACE was evaluated for BCLM; patients treated with TACE had higher response rates and better survival (Li et al 2005;Schneebaum et al 1994;Vogl et al 2010). Li et al (2005) compared results of TACE (n = 28) and systemic chemotherapy (n = 20) and concluded that there was statistically significant differences between the two groups in terms of response rates and survival rates.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, minimally invasive therapy methods such as radiofrequency ablation (RFA), laser-induced thermotherapy (LITT) and transarterial chemoembolization (TACE) have been used for effective and relatively simple treatment of liver metastases from breast cancer (Jakobs et al 2009;Mack et al 2004;Vogl et al 2010;Gadaleta and Ranieri 2010). TACE is a local, catheter-based, minimally invasive therapeutic option for unresectable liver tumors and is defined as a selective administration of chemotherapy usually combined with embolization of the vascular supply of the tumor (Vogl et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With surgery, the OS rate is 49-75/41-61% at 3/5 years, respectively, with a median of 3.8-5.3 years (20-24). With TACE, the OS rate was 63-76/13-48% at 1/3 years, respectively (25)(26)(27) (Table II). Although severe adverse effects are rare, Caralt et al reported that 2/12 patients (17%) suffered from bile leakage postoperatively (28).…”
Section: Discussionmentioning
confidence: 99%
“…However, radiofrequency ablation suffers from high recurrence rates (4); whereas transarterial chemoembolization and selective internal radiation therapy are contraindicated in cases of complete portal vein thrombosis or hepatic insufficiency. Additionally, postembolization syndrome is often observed and the effect on survival has yet to be proven in larger clinical trials (5). These treatments are also not generally suitable for metastases outside the liver (2).…”
mentioning
confidence: 99%